Radiation exposure of radiation workers from 1997 – 2006 based on the criteria and working period - toto Trikasjono; Zainul kamal (Indonesian Journal of Pharmacy, 2010)
The external acceptance dose of radiation worker inYogyakarta have been studied.  This  research  was  done  in  this   three  specific  areas  A,B,C,  because  of worker  in  this  trihedral  have  hit  high  probability  radiation  exposure.  Radiation exposure worker were taken from each  worker  who  wears  Thermoluminescent Dosimeteron period 1997-2006. Exposure result of radiation is done every year in  Laboratory  Safety,  Health  and  Environment,  Centre  of  Research  and Development  Safety  Radiation,  National  Nuclear  Energy  Agency.  This  research aim  is  to  know  how  much  exposure  dose  of  radiation  accepted  by  worker radiation weather have been fulfilled or not the system limitation of dose which have  been  specified  by  International  Commission  on  Radiological  Protection (ICRP)  and  or  Nuclear  Energy  Regulation  Agency   and also  determine furthermore  step  to  guarantee  health  and  safety  worker  radiation  worker. Radiation  worker  that  chosen  as  sample  of  research  are  45  workers  that  are radiation worker. Data collection which is used in this research using personnel radiation monitors.  The  result  of  this  analysis  indicate  that  distribution acceptance of annual dose personal of group interval 0-2 mSv, and acceptance of highest dose 6.09 mSv in the year 1998 from section A. Whole acceptance of dose of external personal at worker from third monitored area, still below the dose  of  limitation  Nuclear  Energy  Regulation  Agency  which  is  recommended  is 50 mSv/year and ICRP 1990 is 20 mSv/year.Key words: personal radiation exposure, radiation worker, radiation